جماعة الإخوان المسلمين في ليبيا 1949-1968: مسارات تأسيسها ومواقفها وردود فعل السلطات المحلية والإقليمية والدولية إزاءها - بو أفرج، وليد شعيب آدم (جامعة طبرق, 2021)
The objective of this research is to shed light, about, the history of Muslim Brothers on the pathways of their creation in Libya, their positions, and, the reactions of local, regional and international authorities to it 1949 1968. We studied, the most important factors that, helped spread their ideas among the Libyan elite. We also discussed the historical aspect, the impact of the asylum of young Egyptian Muslim Brothers in Libya and their role. Then, the training of young people in leadership. Also, the reaction of King Idriss and the Egyptian authorities to them. Then, their position, towards, the monarchical system. Finally, Their activities, and the diplomatic, of the great powers, those, American and British, either in Libya, or from London or Washington.
يتناول البحث مسارات تأسيس جماعة الإخوان المسلمين في ليبيا ومواقفها، وردود فعل السلطات المحلية والإقليمية والدولية حيالها 1949-1968، فضلا عن ملامسة أهم العوامل التي ساعدت على انتشار أفكارها وامتدادها بين النخبة المثقفة في ليبيا. أيضا يتناول ملابسات لجوء شبان جماعة الإخوان المصرين الثلاثة إلى ليبيا وردود فعل الأمر إدريس السنوسي والمؤتمر الوطني البرقاوي والسلطات المصرية حيالهم، وأخيرا يركز على تأسيس جماعة الإخوان تنظيم قيادي في ليبيا وموقفهم من النظام الملكي وقتذاك، ومتابعة الدبلوماسيين الأمريكيين والبريطانيين في ليبيا ولندن وواشنطن لنشاطهم ومساراتهم.
Keywords: تاريخ ليبيا -- الإسلام السياسي -- الجماعات الإسلامية -- جماعة الإخوان المسلمون -- إدريس السنوسي، ملك ليبيا، ت. 1983 م